International Encyclopedia of Geography 2016
DOI: 10.1002/9781118786352.wbieg0179
|View full text |Cite
|
Sign up to set email alerts
|

Distance Decay

Abstract: Distance decay has long been used in geography to describe the effect of distance on cultural or spatial interactions between places. It is an important precept of spatial analysis, especially for spatial interaction models and notions of cultural diffusion. With the advent of transportation and communication technologies, the effect of mere physical distance has been diminishing and a new perspective needs to be developed for the key variables affecting the decay of spatial interactions. Besides, the increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
2
9
0
1
Order By: Relevance
“…We found that people living closer to the store where they were surveyed tended to shop there more often and purchased the highest proportion of foods from that store when compared to customers living further from the store. This idea is consistent with the distance decay theory, which suggests that the interaction among two entities decreases as distance increases (39) . Our finding that shopping frequency was not a statistically significant mediator between distance to the store and dietary outcomes, but that frequency was statistically significantly associated with distance, may suggest that the influence of distance and frequency are interconnected but also distinctly relevant.…”
Section: Discussionsupporting
confidence: 89%
“…We found that people living closer to the store where they were surveyed tended to shop there more often and purchased the highest proportion of foods from that store when compared to customers living further from the store. This idea is consistent with the distance decay theory, which suggests that the interaction among two entities decreases as distance increases (39) . Our finding that shopping frequency was not a statistically significant mediator between distance to the store and dietary outcomes, but that frequency was statistically significantly associated with distance, may suggest that the influence of distance and frequency are interconnected but also distinctly relevant.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research also suggested that accessibility was among several important factors that influence participation in a cost-offset CSA (CO-CSA) program aimed at reaching low-income individuals (White et al, 2018). This aligns with the geospatial distance decay theory or "friction of distance," where the interaction among two entities decreases as distance increases (Pun-Cheng, 2016). Thus, the further away a person lives from a CSA pickup, the less likely the person is to purchase the CSA, or once purchased, the less likely he or she is to pick it up regularly.…”
Section: Introduction and Literature Reviewsupporting
confidence: 75%
“…Travel distance and time are widely recognized factors impacting patients’ access to medical services and their willingness to receive treatment. Residing a long distance from health facilities decreases health service utilization [ 1 3 ]—a phenomenon known as the distance decay effect [ 4 ]. Extended travel distances to therapy or inconvenient care locations are barriers to patient care, particularly for those receiving later-line oncology therapy who may have poorer performance status.…”
Section: Introductionmentioning
confidence: 99%